Correction to Blow-up directions at space infinity for solutions of semilinear heat equations - Noriaki Umeda; Yoshikazu Giga (Boletim da Sociedade Paranaense de Matemática, 2006)
This work presents corrections to "Blow-up directions at space infinity for solutions of semilinear heat equations" published in BSPM 23(2005), 9-28.